Addition effects of erbia-stabilized bismuth oxide on ceria-based carbonate composite electrolytes for intermediate temperature--solid oxide fuel cells - Baek, Seung-Seok; Lee, Naesung; Kim, Byung-Kook; Chang, Haejung; Song, Sun-Ju; Park, Jun-Young (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Highly conductive Er0.2Bi0.8O1.5 (ESB) and rare-earth doped ceria solid oxide electrolytes (SOEs) at intermediate temperature (IT) continue to suffer disadvantages in terms of thermodynamic instability and significant electronic conduction, respectively, at low oxygen partial pressure for solid oxide fuel cell (SOFC) operations. It is therefore necessary to improve the low-temperature ionic conductivity in order to enhance the electrolytic domain of these materials and thereby mitigate cell efficiency dissipation by electronic conduction. In this work, an advanced multiphase carbonate composite material based on ceria has been developed to overcome this IT-SOE challenge. This advanced electrolyte is comprise of nanostructured neodymium-doped ceria (NDC) and 38 wt% (Li-0.5Na)(2)CO3 carbonate with a small amount of ESB phase. The addition of 2 wt% ESB in ceria-based materials decreases the grain boundary resistance of the SOEs in the IT range. Further, a small amount of highly conducting ESB phase in the NDC/[(Li-0.5Na)(2)CO3] composite electrolyte increases the overall conductivity of the composite SOEs. The NDC electrolyte containing 38 wt% carbonate shows the highest conductivity of 0.104 Scm(-1) at 600 degrees C, while the conductivity is increased to 0.165 Scm(-1) by the addition of 2 wt% ESB. In addition, the activation energy of the multiphase composite electrolytes (0.52 eV) is lower than that of the NDC/carbonates (0.65 eV) in the IT range. This is attributed to the effect of the physical properties of the NDC sample, induced by the light ESB doping, on the ionic conductivity, and this effect is closely associated with the grain boundary property. Furthermore, the interfacial effects of the multiphase materials also contribute to the improved conductivity of this advanced composite electrolyte. Copyright (c) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: EFFECTIVE SINTERING AID; DOPED CERIA; IONIC-CONDUCTIVITY; SPACE-CHARGE; ELECTRICAL-CONDUCTIVITY; GD